Enhanced optical functionalities in silica by doping with Au‐based nanostructures. Issue 1 (21st November 2014) - Cesca, Tiziana; Kalinic, Boris; Maurizio, Chiara; Scian, Carlo; Battaglin, Giancarlo; Mazzoldi, Paolo; Mattei, Giovanni
<x xml:space="preserve">Abstract</x> The sensitization mechanism of Er<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh31k51r9t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3+</alternatives> ions by sub‐nanometric Au<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh31k51r1d" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />N</alternatives> aggregates formed in silica by sequential ion implantation has been investigated by room temperature photoluminescence characterizations. Er–Au co‐implanted samples with different Au and Er relative concentrations have been studied. The results allowed to point out a correlation between the luminescence properties of the molecule‐like Au<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh31k51r2z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />N</alternatives> nanoclusters and the Er sensitization effect and to definitely prove the short‐range nature of the energy‐transfer process.<inline-graphic xlink:href="ark:/27927/pgh31k51bn4" content-type="pssb201400106-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Efficient sensitization of the Er<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh31k51r5m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3+</alternatives> luminescence in silica is obtained by energy‐transfer from ultra‐small Au<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh31k51r7q" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />N</alternatives> nanoclusters.